INNOVATIVE APPROACHES TO MILITARY TRAINING: ADVANCEMENTS IN MILITARY DIDACTICS AND INSTRUCTIONAL STRATEGIES - Ziyadullaev Abduqaxxar Shamsievich; Norgitov Farxod Tulkinovich (Journals Park Publishing, 2024)
This article explores the innovative approaches to military training with a focus on advancements in military didactics and instructional strategies. Modern military training demands a shift from traditional methods to more dynamic, technology-driven techniques that enhance the efficiency and effectiveness of military personnel. The study reviews contemporary instructional strategies, such as simulation-based training, e-learning platforms, and adaptive learning systems, which are increasingly being integrated into military education. Furthermore, it examines the impact of these advancements on the cognitive and physical preparedness of soldiers. The findings highlight the benefits of incorporating these modern methods, including improved engagement, retention, and practical application of skills in real-world scenarios. The article concludes with recommendations for implementing these innovative strategies in military training programs to better prepare personnel for the complexities of modern warfare.
Keywords: Military training, military didactics, instructional strategies, simulation-based training, e-learning, adaptive learning, military education, cognitive preparedness, technology-driven training, modern warfare.